Pseudoparaphysanthus linisii (Neckeraceae), a new combination and a new record for mainland South-east Asia. (3rd April 2018) - He, Si; Sukkharak, Phiangphak; Chantanaorrapint, Sahut
Abstract : Stereophyllum linisii Enroth & B.C.Tan (Stereophyllaceae), a rheophytic species, is transferred as Pseudoparaphysanthus linisii (Enroth & B.C.Tan) S.He, Sukkharak & Chantanaorr. (Neckeraceae). The new combination belongs to the recently segregated genus that was established among Neckeropsis sect. Pseudoparaphysanthus . The species has recently been discovered in Thailand and thus new to mainland South-east Asia, representing the first record outside the type locality in the Philippines. Along with the description based on the Thai collection, light microscope photographs of the features of morphological importance and line drawings of the phyllotaxy of this species as well as a key to the genus Pseudoparaphysanthus are provided.